Microwave-Assisted Synthesis of Acetophenone (per-O-acetylated-β-D-glucopyranosyl)thiosemicarbazones - Nguyen Dinh Thanh; Nguyen Thi Kim Giang; Le The Hoai (E-Journal of Chemistry)
Thirteen new substituted acetophenone (2,3,4,6-tetra-O-acetyl-β-D-glucopyranosyl)-thiosemicarbazones (3) were synthesized by reaction of 2,3,4,6-tetra-O-acetyl-β-D-glucopyranosyl thiosemicarbazide (1) and substituted acetophenones (2). The reaction was performed using microwave-assisted method. The compounds (3) have remarkable antibacterial and antifungal activities against Escherichia coli, Staphylococcus epidermidis and Candida albicans.